The evolution of productivity performance on China's dairy farms in the new millennium - Ma, H.; Oxley, Leslie; Rae, A.; Fan, C.; Huang, J.; Rozelle, S. (2012)
China's dairy farm structure has experienced fundamental changes across farm types. As the number of backyard farms has dramatically declined, the share of dairy cows from backyard farms has decreased by 22.4% from 2003 to 2008. However, the herd numbers of larger dairy farms have increased. In particular, the share of dairy cows has risen by 18.8% on small farms, by 22.2% on medium farms, and by 80.8% on large farms over the same period. Total factor productivity was decomposed into technical efficiency and technological change on China's dairy farms using the stochastic production frontier framework. The estimated results indicate that patterns of productivity growth appear to have shifted in the 2000s compared with the 1990s, from generally driven by technological change to exclusively driven by technological change on backyard and small farms and uniquely driven by the improvement of technical efficiency on large farms. Tests of the econometric assumption indicate that the variations in total factor productivity growth patterns across farm types and regions are likely caused by the feed input biases and cropping production practice. © 2012 American Dairy Science Association.